ALTGLAS, VÉRONIQUE. JUDAIZING CHRISTIANITY AND CHRISTIAN ZIONISM IN NORTHERN IRELAND: FOR GOD, ISRAEL, AND ULSTER.1a ED. LONDRES: ROUTLEDGE, 2025. 306P. - Topel, Marta Francisca (Debates do NER, 2026)
-